2010
DOI: 10.1136/adc.2009.175927
|View full text |Cite
|
Sign up to set email alerts
|

Fatness leads to inactivity, but inactivity does not lead to fatness: a longitudinal study in children (EarlyBird 45)

Abstract: Objective To establish in children whether inactivity is the cause of fatness or fatness the cause of inactivity. Design A non-intervention prospective cohort study examining children annually from 7 to 10 years. Baseline versus change to follow-up associations were used to examine the direction of causality. Setting Plymouth, England. Participants 202 children (53% boys, 25% overweight/ obese) recruited from 40 Plymouth primary schools as part of the EarlyBird study. Main outcome measures Physical activity (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
169
1
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(195 citation statements)
references
References 31 publications
15
169
1
10
Order By: Relevance
“…A recent meta-analysis of randomized controlled trials determined that school-based physical activity interventions did not improve BMI compared to pre-existing physical education activity, thereby suggesting that mandated increased physical activity does not have a significant effect on preventing childhood obesity (Harris et al 2009). This result is consistent with a more recent non-intervention prospective study examining children between 7 and 10 years of age suggesting that physical inactivity is the result rather than the cause of childhood obesity (Metcalf et al 2011). While many obesity interventions have focused only on behavioral change in relation to more appropriate eating and exercise habits, few interventions have taken into consideration the emerging role of obesity susceptibility genes and interaction with environmental factors.…”
Section: Preventative Lifestyle Intervention For Common Childhood Obesupporting
confidence: 87%
“…A recent meta-analysis of randomized controlled trials determined that school-based physical activity interventions did not improve BMI compared to pre-existing physical education activity, thereby suggesting that mandated increased physical activity does not have a significant effect on preventing childhood obesity (Harris et al 2009). This result is consistent with a more recent non-intervention prospective study examining children between 7 and 10 years of age suggesting that physical inactivity is the result rather than the cause of childhood obesity (Metcalf et al 2011). While many obesity interventions have focused only on behavioral change in relation to more appropriate eating and exercise habits, few interventions have taken into consideration the emerging role of obesity susceptibility genes and interaction with environmental factors.…”
Section: Preventative Lifestyle Intervention For Common Childhood Obesupporting
confidence: 87%
“…However, recently this assumption has been challenged and some have suggested that physical activity at baseline is unrelated to weight gain at follow-up, but that the converse was true, since greater adiposity levels at baseline was significantly related to lower levels of physical activity or an increased risk of becoming sedentary at follow-up, suggesting reverse causality (35,51,52) . Kwon et al (51) examined the associations between objectively measured time in MVPA by accelerometry, with gain in fat mass in 326 US children, in which objectively measured physical activity and fat mass was available at three time points.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…The most recent studies involve continuous monitoring of movement with accelerometers, allowing detailed analysis of both total and intensity of activity throughout the day, and dual-energy X-ray absorptiometry measures of fatness. Two UK longitudinal studies have used these approaches: the Avon Longitudinal Study of Parents and Children (ALSPAC), a large birth cohort study that has reported on 12-to 14-year-old children (93 -95) ; and the smaller EarlyBird prospective cohort study of 5-to 10-year-olds (96,97) .…”
Section: Direct Evidence Of Physical Activity -Weight Gain Interactionsmentioning
confidence: 99%
“…What was shown, however, was that the higher activity was associated with an improved metabolic score (insulin resistance, TAG, cholesterol:HDL ratio and blood pressure). In a subsequent analysis of the cohort (n 202) between the ages of 7 and 10 years (97) both total and MVPA and body fat (percentage body weight) were measured annually. Although cross-sectional analyses of either total physical activity or MVPA with fatness showed inverse relationships at each age and when time-lagged by^1, 2 and 3 years, when the direction of these relationships was examined in terms of the change in either physical activity or fatness as outcomes, regressed against the other variable as predictor, percentage body fat emerged as the significant negative predictor of the change in physical activity (especially MVPA), not the other way round.…”
Section: Direct Evidence Of Physical Activity -Weight Gain Interactionsmentioning
confidence: 99%